Metabolic Interactions in the Tumor Microenvironment. Issue 11 (November 2017) - Lyssiotis, Costas A.; Kimmelman, Alec C.
Abstract : Tumors are dynamic pseudoorgans that contain numerous cell types interacting to create a unique physiology. Within this network, the malignant cells encounter many challenges and rewire their metabolic properties accordingly. Such changes can be experienced and executed autonomously or through interaction with other cells in the tumor. The focus of this review is on the remodeling of the tumor microenvironment that leads to pathophysiologic interactions that are influenced and shaped by metabolism. They include symbiotic nutrient sharing, nutrient competition, and the role of metabolites as signaling molecules. Examples of such processes abound in normal organismal physiology, and such heterocellular metabolic interactions are repurposed to support tumor metabolism and growth. The importance and ubiquity of these processes are just beginning to be realized, and insights into their role in tumor development and progression are being used to design new drug targets and cancer therapies. Trends: The tumor microenvironment is characterized by deregulated metabolic properties. Intrinsic features (e.g., genetic programs in cancer cells) and extrinsic characteristics (e.g., oxygen tension, nutrient availability, pH) contribute to the deregulated metabolic profile of a tumor. Malignant cells adapt through symbiotic metabolic interactions with other tumor cells. These processes in tumors are repurposed pathways of normal heterocellular metabolic crosstalk. Nutrient competition in the tumor microenvironment impairs effective antitumor immunity.